Obstacle Avoidance Line Following Vehicle - Tuan Daud, Tuan Nur Affiq; Azman, Ammar Yasier (2016)
Car is one of the type of vehicles that used by people to travel from one location to another. Car also is the most favorite vehicle in the community among the other type of vehicles because of its facilities and benefits. However, cars can also bring problems to the consumer. Main problem such as driver’s attitude, range age for driver and energy’s level can affect driving process and can bring harm to the driver, passengers and another car’s consumer on the road. An idea to overcome these problem had to be invented since this problem can cause accident and bring harm to other road users. Hence, in this project, a prototype car with sensors had been designed to overcome the problems occur. The prototype car with help of sensors can automatically move on the road. This will solve problem of limitation of energy from the car driver and accident scenario can be decreased. Other than that, the prototype car can also perform action of avoiding obstacle on the road. With help of sensors to detect the obstacle, the car can make avoiding action without using man’s control. This facility will overcome problem of reckless, careless and dangerous driving on the road and chances of accident happen because these problems can be avoided. Thus, the invention of Obstacle Avoidance Line Following Vehicle project can improve the car facilities for the advantage of the community